AB0932 Sapho syndrome - comparison of different methods of imaging of sterno-clavicular joints. (23rd January 2014) - Przepiera-Bedzak, H.; Cyrylowski, L.; Brzosko, I.; Brzosko, M.
Abstract : Background: SAPHO syndrome is an uncommon but recognized subgroup of psoriatic arthritis and is characterized by dermatological symptoms such as palmo-plantar pulstulosis and acne and osteoarticular symptoms. Radiographic assessment belongs to the diagnostic procedures of SAPHO syndrome although the present of them doesn't belong to diagnostic criteria. Objectives: To compare usefulness different methods of imaging of sterno-clavicular joints in SAPHO syndrome Methods: We studied 15 patients (14 female, 1 male) with confirmed diagnosis of SAPHO syndrome. 14 patients had palmo-plantar pustulosis, 1 patient had severe acne. All of patients had pain and swelling of sterno-clavicular joints. Mean age of patients was 50, 4±12, 1 years, mean disease duration was 2, 9 ± years. All of patients underwent bone scintigraphy, routine x-ray and computed tomography (CT) of sterno-clavicular joints. Results: Increased tracer uptake on bone scintigraphy was found in 13(86, 7%) of patients. In 9 of them in sterno-clavicular joints, in 4 – in sacroiliac joints and in 2 – in peripheral joints. Routine x-ray assessment of sterno-clavicular joints presented abnormalities in 4(26, 7%) patients. These were: clavicle enlargement (1 patient), erosions with hyperostosis (1 patient), irregular calcifications (1 patient), irregular surface of clavicles (1 patient). Computed tomography of sterno-clavicular joints presented abnormalities in 6(40%) patients. These were: erosions (4 patients), hyperostosis (3 patients) and geodes (1 patients). All of patients with abnormal result in CT had increased tracer uptake on bone scintigraphy. Four of them had abnormal result on routine x-ray. Two of them had no changes on routine x-ray. Conclusions: In patients with SAPHO syndrome routine x-ray in not sensitive and seems not necessary in diagnostic procedures. CT assessment is more sensitive in this group of patients. Bone scintigraphy is very sensitive but it could be nonspecific. References: Przepiera-Bedzak H, Brzosko I, Flicinski J, Samborski W, Brzosko M: SAPHO syndrome – Clinical features. Pol Arch Med Wewn2006 116(6): 1172-7. Colina M, Govoni M, Orzincolo C, Trotta F: Clinical and radiological evolution of synovitis, acne, pulstulosis, hyperostosis and osteitis syndrome: a single center study of a cohort of 71 subjects. Arthritis Rheum 2009; 61(6): 813-21. Salles M, Olive A, Perez-Andres R, Holgado S, Mateo L, Riera E, Tena X: The SAPHO syndrome: a clinical and imaging study. Clin Rheumatol 2011; 30: 245-9. Disclosure of Interest: None Declared